Museum Objects as Accidental Refugees - Appadurai, Arjun (Historische Anthropologie, 2017)
It is now commonly said that objects are mobile, animate and agentive subjects, which are capable of expressing purpose, desire and telos. This insight has been interactively produced by scholars from across a range of disciplines, from science and technology studies, such as Bruno Latour, and media studies, such as Jussi Parikka to art criticism, anthropology, political theory and feminist theory. My own 1986 book on The Social Life of Things was an early indicator of this point of view. Today, the debate about the line between human and non-human actors has become part of bigger debates about climate change, the Anthropocene, robotics, informatics, the life sciences and more. So the concern of curators, ethnologists and museum professionals with how to curate, represent and display objects has become inevitably more heated and controversial. Furthermore, the building of all Western ethnological collections is inevitably tied up with difficult issues of conquest, commerce and power in the age of empire.